2019
DOI: 10.3390/rs11232849
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Particulate Organic Carbon in Coastal Waters from Remote Sensing: Inter-Comparison Exercise and Development of a Maximum Band-Ratio Approach

Abstract: Recently, different algorithms have been developed to assess near-surface particulate organic matter (POC) concentration over coastal waters. In this study, we gathered an extensive in situ dataset representing various contrasted bio-optical coastal environments at low, medium, and high latitudes, with various bulk particulate matter chemical compositions (mineral-dominated, 50% of the data set, mixed, 40%, or organic-dominated, 10%). The dataset includes 606 coincident measurements of POC concentration and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The BG algorithm was established using in situ POC concentrations ranging from 12 to 270 mg/m 3 , and the CI POC algorithm was established using in situ POC concentrations less than 1000 mg/ m 3 . As a result, the BG and CI POC algorithms had significant errors in coastal waters with complex optical environments (Duan et al, 2014;Evers-King et al, 2017;Le et al, 2017;Le et al, 2018;Lin et al, 2018;Jiang et al, 2019;Tran et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The BG algorithm was established using in situ POC concentrations ranging from 12 to 270 mg/m 3 , and the CI POC algorithm was established using in situ POC concentrations less than 1000 mg/ m 3 . As a result, the BG and CI POC algorithms had significant errors in coastal waters with complex optical environments (Duan et al, 2014;Evers-King et al, 2017;Le et al, 2017;Le et al, 2018;Lin et al, 2018;Jiang et al, 2019;Tran et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several bio-optical algorithms have been created to estimate the Particulate Organic Carbon (POC) concentration in oceanic layers [66][67][68][69][70] and eutrophic lakes [71]. These algorithms were obtained for band ratios corresponding to red-to-blue (R 665 /R 490 ), red-to-green (R 665 /R 560 ), or blue-to-red (R 490 /R 665 ) for ocean studies and for blue-to-green (R 443 /R 560 and R 490 /R 560 ) ratios for lake studies.…”
Section: Discussionmentioning
confidence: 99%
“…A further five ratios in Figure 10 represent blue-to-red R rs band ratios which do not have any standard global application in bio-optical algorithms in the ocean, however they are used locally in coastal waters, e.g., to derive surface concentrations of suspended particulate matter (SPM) and particulate organic carbon (POC) [71,73]. We found that there are R rs band ratios affected by all or most types of investigated oils.…”
Section: "Blue-to-red" R Rs Ratiosmentioning
confidence: 99%